Prevalence of hepatitis A virus and hepatitis E virus in the patients presenting with acute viral hepatitis in Rohtak, Haryana, India - Rawat, Sarita; Gill, P. S.; Gupta, Tanuj; Malhotra, Praveen; Parmar, Aparna (International Journal of Research in Medical Sciences, 2019)
Background: Hepatitis A virus (HAV) and hepatitis E virus (HEV) cause acute hepatitis in humans and are transmitted mainly through the fecal-oral route. They pose major health problems in developing countries. This study was done to determine prevalence of HAV and HEV in patients presenting with AVH and the co-infection of HAV and HEV in these patients. Methods: The study was conducted in the virology research and diagnostic laboratory, PGIMS Rohtak during the study period of August 2017-December 2018. The study population included sera of individuals from all age group who were suspected of acute viral hepatitis (AVH). All the sera were screened for IgM antibody to HEV and HAV using IgM capture ELISA. Results: HEV IgM ELISA test was performed in 307 patients (mean age 34 years;), with an overall seroprevalence rate of 138(44.9%). HAV antibodies were detected in 109 subjects, with a median age of 9.5 years the seroprevalence of HAV was 34 (31.1%). HEV seropositivity was highest in the age group 20-30 years. Mean age was 34 years whereas the interquartile range was from 14-71 years. HAV infection was positive mainly in the age group <10 years. With interquartile range from 6-16 years. Out of total 34 patients positive for HAV infection males were 20 (58.8%), whereas females were 14(41.1%). HEV IgM was positive in 138 patients, out of which male were 96 (69.56%) and females were 42 (30.43%). HEV IgM was positive in 138 patients, out of which male were 96 (69.56%) and females were 42 (30.43%). HAV and HEV seen to be prevalent all with highest predominance seen towards the end of monsoons (August and September) and beginning of winters. Conclusions: The present study also points toward HEV being the prime etiological agent for outbreaks of acute hepatitis in the studied region of Haryana (Rohtak), India. A comparatively lower HAV prevalence may be the consequence of an overall declining trend due to improved living standards and environmental hygiene.